Morin hydrate inhibits influenza virus entry into host cells and has anti-inflammatory effect in influenza-infected mice - Hong, Eun Hye; Song, Jae Hyoung; Kim, Seong Ryeol; Cho, Jaewon; Jeong, Birang; Yang, Heejung; Jeong, Jae Hyeon; Ahn, Jae Hee; Jeong, Hyunjin; Kim, Seong Eun; Chang, Sun Young; Ko, Hyun Jeong (Immune Network, 2020)
Influenza virus is the major cause of seasonal and pandemic flu. Currently, oseltamivir, a potent and selective inhibitor of neuraminidase of influenza A and B viruses, is the drug of choice for treating patients with influenza virus infection. However, recent emergence of oseltamivir-resistant influenza viruses has limited its efficacy. Morin hydrate (3,5,7,2′,4′-pentahydroxyflavone) is a flavonoid isolated from Morus alba L. It has antioxidant, anti-inflammatory, neuroprotective, and anticancer effects partly by the inhibition of the NF-кB signaling pathway. However, its effects on influenza virus have not been studied. We evaluated the antiviral activity of morin hydrate against influenza A/Puerto Rico/8/1934 (A/ PR/8; H1N1) and oseltamivir-resistant A/PR/8 influenza viruses in vitro. To determine its mode of action, we carried out time course experiments, and time of addition, hemolysis inhibition, and hemagglutination assays. The effects of the co-administration of morin hydrate and oseltamivir were assessed using the murine model of A/PR/8 infection. We found that morin hydrate reduced hemagglutination by A/PR/8 in vitro. It alleviated the symptoms of A/PR/8-infection, and reduced the levels of pro-inflammatory cytokines and chemokines, such as TNF-α and CCL2, in infected mice. Co-administration of morin hydrate and oseltamivir phosphate reduced the virus titers and attenuated pulmonary inflammation. Our results suggest that morin hydrate exhibits antiviral activity by inhibiting the entry of the virus.
Keywords: Antivirals; Hemagglutinin; Influenza A Virus; Morin hydrate; Oseltamivir